ASSESSMENT OF OCCUPATIONAL EXPOSURES TO ANTINEOPLASTIC DRUGS IN A HOSPITAL OF HIGH COMPLEXITY - Pontes, André Teixeira (2015)
The hospital sector has been considered one of the most susceptible to occupational exposures, because has various patient’ groups with various infectious diseases and carry out many procedures with risk of accidents and diseases for healthcare professionals. Among the factors that most affect health workers can stand out chemical factors such as antineoplastic agents that expose the trader to different forms of contamination. This study features a case study in a university hospital with a high complexity oncology sector to assess the occupational risk levels involved in the activities carried out. We emphasize that in any of the activities analyzed the risk can be considered negligible. Regarding consequences and the probability associated to the occurrence of the risk, it was observed that half the activity is associated with risks routine and a considerable number of these high risk is therefore allowing classifies them as non-tolerable risks. In conclusion, we note that the methodology used for risk assessment in hospitals, being a useful tool and an important source of information for managers to promote the implementation of improvements in hospital processes in order to minimize the risks to which professional’s health are exposure.